2016
DOI: 10.1039/c6sc00077k
|View full text |Cite
|
Sign up to set email alerts
|

Heteronanowires of MoC–Mo2C as efficient electrocatalysts for hydrogen evolution reaction

Abstract: MoC–Mo2C heteronanowires accomplished via controlled carbonization are efficient in the hydrogen evolution reaction due to a synergistic enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
344
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(355 citation statements)
references
References 49 publications
11
344
0
Order By: Relevance
“…We further found that there are plenty of dots in HAADF‐STEM image of the SL‐MoO x NS (Figure S6, Supporting Information), which means the SL‐MoO x NS is formed by these small clusters steadied by glycine. Therefore we suppose that the MoO x HNS should be formed undergoing four steps: at the beginning of the reaction, the ammonium heptamolybdate and glycine combine to form the organic‐inorganic hybrids in the acidic conditions; then the hybrids dissolve and the molybdenum‐oxygen clusters generate; after that, these clusters arrange together and the SL‐MoO x NS is formed; finally, the SL‐MoO x NS assemble to the MoO x HNS.…”
Section: Resultsmentioning
confidence: 99%
“…We further found that there are plenty of dots in HAADF‐STEM image of the SL‐MoO x NS (Figure S6, Supporting Information), which means the SL‐MoO x NS is formed by these small clusters steadied by glycine. Therefore we suppose that the MoO x HNS should be formed undergoing four steps: at the beginning of the reaction, the ammonium heptamolybdate and glycine combine to form the organic‐inorganic hybrids in the acidic conditions; then the hybrids dissolve and the molybdenum‐oxygen clusters generate; after that, these clusters arrange together and the SL‐MoO x NS is formed; finally, the SL‐MoO x NS assemble to the MoO x HNS.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b The X-ray photoelectron spectroscopy (XPS) was conducted to investigate the chemical composition and valence state of the transition metals in the samples. [57,58] The Ni/Mo 2 C(1:2)-NCNFs exhibits Mo 3d 5/2 and Mo 3d 3/2 peaks for Mo 2+ at 228.4 and 231.6 eV. The Mo 4+ and Mo 6+ species should originate from the inert MoO 2 and MoO 3 components, respectively, which can be ascribed to a partial surface oxidation of MoC x in air.…”
Section: Morphological and Structural Characterizationsmentioning
confidence: 99%
“…Especially, Mo 2 C has been found to exhibit electrocatalytic performances for HER due to the high conductivity, similar d-band electronic density-of-state to that of Pt and optimal hydrogen-adsorption energy [24]. For instance, Lan et al reported Mo 2 C supported on reduced graphene oxide with low onset overpotential for HER [25].…”
Section: Introductionmentioning
confidence: 98%